The Incidence of Salmonella and E. Coli in Poultry feeds - Okoye, Patience; Ezemba, Contance chinyere; Ezemba, Constance Chinyere; Obi , Chisom Perpetua; Eleanya, Lilian Chinyere; Udoye, Ifunanya; Ezemba, Arinze Steven; Osuala, Oluchi Judith; Archibong, Etim Joseph (Journal of Current Biomedical Research, 2021)
Raw poultry and meat products consumption remain the principal source of Salmonella and E. coli in many countries. Salmonella has been reported in a variety of chicken, turkey and other meat products. Poultry is frequently colonized with Salmonella without detectable symptoms. This constitutes health risk not only for the animal but also for humans. This study was designed to help in achieving one health. Eight different brands of poultry feed samples were aseptically collected from the different poultry farms and poultry market places in Anambra State. From the result, feed sample D (layer) had the highest viable bacteria count which was too numerous to count and the lowest was found in sample E which was 3.33x106 CFU/g. The highest coliform count was found in sample H with 1.19 x107 CFU/g and the lowest was seen in sample A with 3.7x106 CFU/g. The bacteria viable count with the highest Salmonella was found in sample D (layer) and Escherichia coli in sample H. The bacteria percentage of Salmonella was 62.5% and E. coli was 100% from different feed samples. With the high presence of the pathogens in the feeds, there is need for good manufacturing practice, handling and retailing methods to enhance the microbiological quality of these feeds.